Stakeholders’ Perception of Online Instruction within COVID-19 Pandemic - Editor, Chatchawan Changphat; Tanapat Tiamklee; Niracha Kimratchot; Monthira Prasoetthai; Veena Prachagool; Prasart Nuangchalerm (Journal of Educational Issues, 2024)
This study employed survey research, aims to study opinions of students, teachers, and parents on teaching and learning online within COVID-19 pandemic. The research gathered data from 99 stakeholders which consisted of teachers, students, and parents. Questionnaire was designed for asking their opinions by dividing it into 4 dimensions. Findings showed that students’ dimension was at high level, but other dimensions; teachers, parents, and learning environment were at medium level. The level of opinion in each dimension seem to be different, ANOVA was employed for analyzing mean differences. The result showed that there was significantly difference at .05 level of statistics. It can be concluded that students’ dimension had mean difference with teachers and parents’ dimension; teachers’ dimension had mean difference with students, parents, and learning environments’ dimension; parents’ dimension had mean difference with students, teachers, and learning environments’ dimension; and learning environments’ dimension had mean difference with teachers and parents’ dimension as well.